Carbonic Anhydrase IX Targeted Polyaspartamide fluorescent Probes for Tumor imaging - Zhang Y; Liu F; Shao C; Huang J; Yan G (International Journal of Nanomedicine)
Yu Zhang,1,2 Fan Liu,2,3,* Chuntao Shao,2,* Jun Huang,3 Guoping Yan1 1College of Chemical and Material Engineering, Quzhou University, Quzhou, Zhejiang Province, 324000, People’s Republic of China; 2School of Materials Science and Engineering, Wuhan Institute of Technology, Wuhan, 430205, People’s Republic of China; 3School of Chemical and Biomolecular Engineering, University of Sydney, NSW, 2006, Australia*These authors contributed equally to this workCorrespondence: Guoping Yan, Tel +86 570 8028560, Email guopingyan@qzc.edu.cnBackground: Precise intraoperative tumor delineation is essential for successful surgical outcomes. However, conventional methods are often incompetent to provide intraoperative guidance due to lack specificity and sensitivity. Recently fluorescence-guided surgery for tumors to delineate between cancerous and healthy tissues has attracted widespread attention. The contrast-enhanced fluorescent imaging has been applied for non-invasive diagnosis of cancers using tumor-targeting fluorescent probes.Methods: The carbonic anhydrase IX targeted polyaspartamide fluorescent compounds (SD-PHEA-NI) were synthesized by incorporating a tumor-targeting group of sulfadiazine (SD) and N-butyl-4-ethyldiamino-1,8-naphthalimide (NI) into water-soluble carriersof poly-α,β-[N-(2-hydroxyethyl)-L-aspartamide] (PHEA). These derivatives were also characterized by Fourier transform infrared spectroscopy, gel permeation chromatography, ultraviolet-visible spectroscopy, nuclear magnetic resonance spectroscopy and fluorescence assays. The cellular uptake, cytotoxicity, and fluorescence imaging ability were evaluated.Results: Experiment results indicated that SD-PHEA-NI has low cytotoxic to Henrietta Lacks (HeLa) cells. Moreover, B16F10 melanoma cells can take up SD-PHEA-NI and show good green fluorescent images. However, SD-PHEA-NI displayed a low-intensity green fluorescence signal in healthy human embryonic kidney (293T) cells.Conclusion: SD-PHEA-NI can be considered a potential fluorescent probe for the detection of tumors. This study has the potential to enhance tumor diagnosis and image-guided surgical interventions by providing real-time information and robust decision support, thereby reducing recurrence and complication rates and ultimately improving patient outcomes.Keywords: fluorescent imaging, polyaspartamide, sulfadiazine, naphthalimide, fluorescent probes